Synthesis and standardization of an impurity of acetaminophen, development and validation of liquid chromatographic method - KULABAŞ, NECLA; KÜÇÜKGÜZEL, İLKAY (My University, 2023)
© 2022 Elsevier B.V.One of the impurities of acetaminophen, N,N\"-(oxydi-4,1-phenylene)diacetamide (ODAA), which is not specified in the organic impurities analysis method of acetaminophen by high performance liquid chromatography (HPLC) in American Pharmacopoeia Version 42 (USP 42), was synthesized, characterized and standardized. A new and optimized liquid chromatographic method for the determination of organic impurities of acetaminophen was developed using an ultra-high performance liquid chromatographic (UHPLC) system, which can separate this impurity. This new liquid chromatographic method has been optimized and validated for the simultaneous determination of acetaminophen related compound B, acetaminophen related compound C, acetaminophen related compound D, acetaminophen related compound J and ODAA, the organic impurities in acetaminophen drug substance. Acetaminophen was also subjected to stress-testing under acidic hydrolysis, alkaline hydrolysis, oxidative degradation, thermal degradation and photolytic degradation for 15 days. The impurity molecule, ODAA was synthesized using 4,4′-oxydianiline and acetic anhydride. The chemical structure of the synthesized ODAA molecule was confirmed by characterization studies. The potency of ODAA was found to be 99.64% as a result of the relevant analyses. The chromatographic separation was achieved on a C8 (150 mm × 2.1 mm; 2-µm particle size) reversed-phase column using a gradient elution, being solvent A: methanol-water-glacial acetic acid (50:950:1, v/v/v) and solvent B: methanol-water-glacial acetic acid (500:500:1, v/v/v) flowing at a rate of 0.2 mL/min. The limits of quantitation (S/N 10:1) were 1.248 µg/mL for acetaminophen, 0.373 µg/mL for acetaminophen related compound B, 1.217 µg/mL for acetaminophen related compound C, 0.369 µg/mL for acetaminophen related compound D, 0.125 µg/mL for acetaminophen related compound J and 0.373 µg/mL for ODAA. The individual mean recoveries of each impurity molecule spiked into acetaminophen samples at different concentration levels ranged from 93% to 104%. The method developed for UHPLC instrument was successfully applied to the analyses of different lots of acetaminophen. Thus, the proposed method can be used for determination of this impurity in the presence of other specified impurities of acetaminophen.
Keywords: Tıp; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Analitik Kimya; Fizikokimya; Spektroskopi; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Analytical Chemistry; Physical Chemistry; Spectroscopy; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Klinik Tıp; TROPİKAL TIP; KİMYA, ANALİTİK; SPEKTROSKOPİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); CLINICAL MEDICINE; CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; TROPICAL MEDICINE; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Fizik Bilimleri; Farmasötik bilim; İlaç Keşfi; Klinik Biyokimya; Physical Sciences; Pharmaceutical Science; Drug Discovery; Clinical Biochemistry; Acetaminophen impurities; N,N'-(oxydi-4,1-phenylene)diacetamide; Standardization; Stress-testing; UHPLC; Validation